Supply and demand matching of public sports services for rural older adults in China: current situation and related factors - Zhang, Hai-pei; He, Cong-hui; Wang, Zhi-hua; LU, Wen-yun (Frontiers in Public Health, 2025)
IntroductionChina's rural aging population faces significant health challenges. This study examines the supply-demand matching of public sports services for rural older adults to promote healthy aging.MethodsWe surveyed adults aged 50+ (demand side) and village cadres (supply side) across eastern, central, and western China. Data were collected via questionnaire surveys and analyzed using canonical correlation analysis (CCA).ResultsOverall supply-demand matching was low, with significant deficiencies in sports funding, facilities, and activity organization. Matching levels were higher in eastern and economically developed villages. Older adults' demand correlated significantly with educational background, economic status, and health conditions. CCA revealed that service matching enhanced physical activity awareness but failed to address needs related to health status and lifestyle, showing notable gaps in satisfaction and participation.DiscussionTo optimize services, we propose improved strategic planning, multi-entity collaboration, demand-oriented content, and integrated online-offline platforms to better support healthy aging in rural China.